Odpowiedź :
Odpowiedź:
[tex]a)\ \ \dfrac{2a-b^2}{4}=\dfrac{2\cdot5-(-3)^2}{4}=\dfrac{10-9}{4}=\dfrac{1}{4}\\\\\\b)\ \ 3,5x+5y=3,5\cdot(-5)+5\cdot2=-17,5+10=-7,5\\\\\\c)\ \ 3x-\frac{1}{2}y=3\cdot6-\frac{1}{\not2_{1}}\cdot(-\not4^2)=18+2=20\\\\\\d)\ \ \dfrac{4}{t+3s}=\dfrac{4}{-3+3\cdot(-2)}=\dfrac{4}{-3-6}=\dfrac{4}{-9}=-\dfrac{4}{9}\\\\\\e)\ \ 3mn+m^2n=3\cdot2\cdot(-6)+2^2\cdot(-6)=6\cdot(-6)+4\cdot(-6)=-36-24=-60[/tex]
[tex]f)\ \ 2r(p+1)^2=2\cdot(-2)\cdot(-4+1)^2=-4\cdot(-3)^2=-4\cdot9=-36\\\\\\g)\ \ \frac{2}{7}(c-2d)^2=\frac{2}{7}(2-2\cdot(-6))^2=\frac{2}{7}(2+12)^2=\frac{2}{7}\cdot14^2=\frac{2}{\not7_{1}}\cdot\not196^2^8=2\cdot28=56\\\\\\h)\ \ 0,2d^2(c-d)=0,2\cdot(-5)^2\cdot(0-(-5))=0,2\cdot25\cdot(0+5)=5\cdot5=25[/tex]